Innovation in low carbon construction technologies: an historic analysis for obviating defects - Alan M. Forster; Scott Fernie; Kate Carter; Peter Walker; Derek Thomson (2015)
Purpose – The purpose of this paper is to evaluate the risks of building defects associated with rapid advancement of “green” construction technologies. It identifies the methods adopted by the sector for the determination of pre-construction defects that are framed within the context of, traditional; scientific; and professional design approaches. These are critically evaluated and utilised in attempts to mitigate defects arising from diffusing low carbon construction innovations. Design/methodology/approach –The paper takes the formof an evaluative literature review. Polemic in orientation, the paper critically compares two periods of time associated with rapid advancement of innovation. The first, the post-Second World War housing boom is synonymous with a legacy of substandard buildings that in many cases rapidly deteriorated, requiring refurbishment or demolition shortly after construction. The second, is today’s “green” technology “shift” with its inherent uncertainty and increased risk of latent building defects and potential failure to deliver meaningful long-term performance. Central to this is an exploration of the drivers for innovation, and subsequent response, precautionary measures initiated, and the limitations of institutionalised systems to identify and mitigate defects. Similarities and differences between these historical periods frame a discussion around the theoretical approaches to defects and how these may be limited in contemporary low carbon construction. A conceptual framework is presented with the aim of enhancing the understanding for obviation of defects. Findings – Sufficient commonality exists between the periods to initiate a heightened vigilance in the identification, evaluation and ideally the obviation of defects. Design evaluation is not expressly or sufficiently defect focused. It appears that limited real change in the ability to identify defects has occurred since the post-war period and the ability to predict the performance of innovative systems and materials is therefore questionable. Attempts to appraise defects are still embedded in the three principle approaches: traditional; scientific; and professional design. Each of these systems have positive characteristics and address defect mitigation within constrains imposed by their very nature. However, they all fail to address the full spectrum of conditions and design and constructional complexities that lead to defects. The positive characteristics of each system need to be recognised and brought together in an holistic system that offers tangible advantages. Additionally, independent design professionals insufficiently emphasise the importance of defect identification and holistic evaluation of problems in design failure are influenced by their professional training and education. A silo-based mentality with fragmentation of professional responsibility debases the efficacy of defect identification, and failure to work in a meaningful, collaborative cross professional manner hinders the defect eradication process. Research limitations/implications – Whilst forming a meaningful contribution to stimulate debate, further investigation is required to tangibly establish integrated approaches to identify and obviate defects. Practical implications – The structured discussion and conclusions highlight areas of concern for industry practitioners, policy makers, regulators, industry researchers and academic researchers alike in addressing and realising a low carbon construction future. The lessons learned are not limited to a UK context and they have relevance internationally, particularly where rapid and significant growth is coupled with a need for carbon reduction and sustainable development such as the emerging economies in China, Brazil and India. Social implications – The carbon cost associated with addressing the consequences of emerging defects over time significantly jeopardises attempts to meet legally binding sustainability targets. This is a relatively new dimension and compounds the traditional economic and societal impacts of building failure. Clearly, blindly accepting this as “the cost of innovation without development” cannot be countenanced. Originality/value – Much research has been undertaken to evaluate post-construction defects. The protocols and inherent complexities associated with the determination of pre-construction defects have to date been largely neglected. This work attempts to rectify this situation.